Elliot, John (2012). Making history. Madrid: Taurus (2014)
Making history is not a biographical testimony in the manner of the one made by Eric Hobsbawm in his interesting years, but an original reflection on the historian's work, the challenges posed by the writing of the past and the current horizon of the hist